2018
DOI: 10.1080/19942060.2018.1453381
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulation of a self-propelled fish-like body swimming in a channel

Abstract: In this study, a three-dimensional simulation of a fish-like body swimming in a channel with non-slip walls was carried out to investigate the effects of kinematics on swimming performance. Selfpropelled swimming in an inertial coordinate system was examined by using the direct forcing immersed boundary method. The fish body consisted of several rigid bodies and behaved analogously to a multi-segment robotic fish. The computational program was first validated by simulating fluid flow around a circular cylinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Moreover, it has been improved upon numerous times since its initial conception [52][53][54][55][56][57][58]115]. It has been previously used in numerous applications ranging from physiological flows, such as those in cardiac fluid dynamics [59][60][61], blood vessels [62], lymphatic capillaries [63], to aquatic locomotion [64][65][66][67] to animal flight [68,69] to flow past biological structures, such as vegetation [70], leaves [71], seeds [72], corals [73], or biofilms [74].…”
Section: Mathematical Methodsmentioning
confidence: 99%
“…Moreover, it has been improved upon numerous times since its initial conception [52][53][54][55][56][57][58]115]. It has been previously used in numerous applications ranging from physiological flows, such as those in cardiac fluid dynamics [59][60][61], blood vessels [62], lymphatic capillaries [63], to aquatic locomotion [64][65][66][67] to animal flight [68,69] to flow past biological structures, such as vegetation [70], leaves [71], seeds [72], corals [73], or biofilms [74].…”
Section: Mathematical Methodsmentioning
confidence: 99%
“…Moreover, it has been improved upon numerous times since its initial conception [50,51,52,53,54,55,56]. It has previously used in numerous applications ranging from physiological flows, such as those in cardiac fluid dynamics [57,58,59], blood vessels [60], lymphatic capillaries [61], to aquatic locomotion [62,63,64,65,66] to animal flight [67,68] to flow past biological structures, such as vegetation [69], leaves [70], seeds [71], or corals [72].…”
Section: Mathematical Methodsmentioning
confidence: 99%
“…Te wave motion pattern of anguilli was optimized and analyzed by Kern and Koumoutsakos [10], and quantitative information of three-dimensional fuid body interactions was provided by current results. Te infuence of the kinematic characteristics of fsh swimming in the water channel with antiskid wall on its swimming performance was discussed by Zhang et al [11] using the threedimensional simulation method. Te results indicated that the thrust generation mechanism was provided by the velocity feld and vorticity feld around the model, and the infuence of kinematics on swimming performance was emphasized.…”
Section: Introductionmentioning
confidence: 99%